Effects of cilostazol for in-stent restenosis after carotid artery stenting: a meta-analysis - Jing Sun; Duo Wang; Yue Zhao; Ying Bai; Chang Meng; Guobin Miao; Peng Liu (Journal of Cardiothoracic Surgery)
Abstract Objectives There is some controversy regarding drug therapy to prevent in-stent restenosis (ISR) after carotid artery stenting. In recent years, cilostazol has received increasing research attention. We performed a meta-analysis to evaluate the effects of cilostazol on the outcome of ISR after carotid stenting. Methods A meta-analysis was carried out to identify the clinical trials that had been published up to 22 December 2024. The databases PubMed, Embase, Cochrane Library, CNKI and Wanfang have all been queried. The study population was composed of patients with stent carotid heart disease who were receiving cilostazol. Results included in-stent-restenosis, ischemic stroke and all-cause mortality. Publications were reviewed according to the Cochrane Handbook and the guidelines set out in the Preferred Reporting Project for Systematic Review and Meta-Analysis (PRISMA 2020). The methodological quality of the studies was assessed using the Revised Cochrane Risk of Bias tool for randomized trials (RoB 2.0) and the Risk of Bias in Non-Randomized Studies of Interventions (ROBINS-I). Results This study was registered with INPLASY (number INPLASY202510004). A total of 1975 patients were included in 4 randomized controlled trials (RCTs) and 5 non-RCTs. A statistically significant reduction in ISR was observed for antiplatelet regimens including cilostazol compared to the control group (OR = 0.27, 95%CI: 0.13 ~ 0.54, P<0.01, I2 = 30%). Subgroup analysis revealed this finding was primarily driven by non-randomized controlled trials (non-RCTs), demonstrating a consistent effect (OR = 0.17, 95%CI: 0.08 ~ 0.39, P<0.01, I2 = 0%). For other primary end events, no significant differences were noted in the incidence of ischemic stroke (OR = 0.83, 95%CI: 0.50 ~ 1.39, P = 0.49, I2 = 0%) or all cause death (OR = 0.53, 95%CI: 0.26 ~ 1.05, P = 0.07, I2 = 0%). The certainty of evidence for the ISR outcome was rated as low. Conclusions Cilostazol was associated with less postoperative carotid stent restenosis, with no statistically significant difference in ischemic stroke and all-cause mortality.